The Efficiency of UTAUT2 Model in Predicting Student’s Acceptance of Using Virtual Reality Technology - Al Farsi, Ghaliya (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In this study, the impact of the theory Unified Theory of Acceptance and Use of Technology UTUAT2 in virtual reality System (VRS) is discussed. Virtual reality (VR) has emerged as a major tool in this field of research and education development.This study integrates UTAUT2 and the learning value architecture to extend the UTAUT2 framework and provides a new perspective on predictions of students' behavior intentions towards and use of VRS. used Method research as an approach to our study by using a closed questionnaire to collect data from many Omani university. The students who have previously used a virtual reality System. This research implemented framework and it was tested and evaluated with satisfactory results using advanced (PLS-SEM) tools.